Endocarditis: An Ever Increasing Problem in Cardiac Surgery - Ostovar, Roya; Schroeter, Filip; Kuehnel, Ralf-Uwe; Erb, Michael; Filip, Tomas; Claus, Thomas; Albes, Johannes M. (The Thoracic and Cardiovascular Surgeon, 2019)
Background Endocarditis remains one of the most threatening diagnoses in cardiac surgery and is still increasing. Particularly, device-related as well as prosthetic endocarditis appears to be on the rise. Early mortality and periprocedural complications are high jeopardizing the success of surgical efforts. We looked at the development of the numbers and the distribution of endocarditis in an all-comer analysis.Methods From 2003 to 2017, 752 patients with endocarditis were transferred to our cardiosurgical institution (mean age 65 ± 13 years; mean logistic EuroSCORE 28.01%; males 74.33%). A total of 89.49% of them were surgically treated; 30.01% redo cases thereof; and 9.17% had been operated previously for acute endocarditis.Results While the total number of cardiosurgical procedures remained relatively stable throughout the years, 20 patients were admitted in 2003 and 79 in 2017 yielding more than fourfold increase (p < 0.001). Early mortality of all patients was 25.1%. Septic emboli occurred in 23.7% and 43.8% cerebral emboli thereof. A significant increase of aortic, mitral, and tricuspid valves involvement was observed (p < 0.001). An increase of device-related endocarditis was also noted (p < 0.001).Conclusion Endocarditis remains a serious problem with high early mortality and morbidity. The vast increase of electrophysiological device implantations has resulted in an increase of tricuspid valve involvement. Liberalization of endocarditis prophylaxis, that is, more restrictive use of antibiotics in 2007 may have at least partially contributed to an increase of the individual risk to suffer from acute endocarditis. A renaissance of a stricter endocarditis–prophylaxis may thus be considered.
Keywords: endocarditis; heart valve; surgery; outcome